T-stub behavior under out-of-plane bending. II: Parametric study and analytical characterization. (1st September 2015) - Gil, Beatriz; Bijlaard, Frans; Bayo, Eduardo
Highlights: Consideration of real behavior of joints under out-of-plane bending can optimize structures. To characterize the behavior, the main components of the T-stub are identified. Analytical expressions for the components and the mechanical model are proposed. The stiffness and strength obtained compare very satisfactorily with experimental results. Abstract: Beam to column connections subjected to loads in the beam minor axis direction are usually considered either as pinned or rigid for both resistance and stiffness checks. This simplification is also assumed at the time of considering the stability of the column and the lateral buckling of the beams. However, as proven in the companion paper by means of laboratory tests and numerical simulations, these types of connections are actually semi-rigid and partial strength. The consideration of their real semi-rigid behavior can lead to a more accurate global analysis and, consequently, more optimized structures. Their behavior relies mainly on the characterization of the components acting on the T-stub under out-of-plane bending. In this paper a parametric analysis is performed to define the components involved. Analytical expressions are specified to describe each one of the components and the assembly process following a proposed mechanical model. The stiffness and strength that are obtained compare very satisfactorily with the experimental results of the T-stubs described in the companion paper.